2015
DOI: 10.1016/j.hlc.2014.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical Cardiac and Cerebral Arterial Gas Embolus During Percutaneous Lead Extraction in a Patient with a Patent Foramen Ovale

Abstract: A 42 year-old man presented for elective percutaneous lead extraction for pacemaker redundancy. The procedure was performed supine under general anaesthesia via the right femoral vein and was complicated by acute inferior ST elevation and hypotension. Urgent transoesophageal echocardiogram showed inferior left ventricular hypokinesis, right ventricular impairment, a patent foramen ovale and air in the left ventricle. Coronary angiography demonstrated normal coronary arteries, the ST changes resolved and the le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 10 publications
0
2
0
1
Order By: Relevance
“…При этом стоит отметить, что воздушная эмболия коронарных сосудов, описанная во всех литературных источни-ках, проявлявшаяся изменениями на электрокардио-граммах и гемодинамической нестабильностью, ре-грессировала в течение небольшого промежутка времени (до 30 мин), на фоне инотропной и инфу-зионной терапии. Также во всех наблюдениях от-мечалось преимущественное попадание воздушных эмболов в правую коронарную артерию [7,8].…”
Section: Discussionunclassified
“…При этом стоит отметить, что воздушная эмболия коронарных сосудов, описанная во всех литературных источни-ках, проявлявшаяся изменениями на электрокардио-граммах и гемодинамической нестабильностью, ре-грессировала в течение небольшого промежутка времени (до 30 мин), на фоне инотропной и инфу-зионной терапии. Также во всех наблюдениях от-мечалось преимущественное попадание воздушных эмболов в правую коронарную артерию [7,8].…”
Section: Discussionunclassified
“…Following the initial management, dual antiplatelet inhibition would be recommended for these patients [107] for a duration of 6-12 months as per the 2017 American College of Cardiology (ACC)/American Heart Association (AHA) Guidelines [108].…”
Section: Clinical Managementmentioning
confidence: 99%
“…It has been reported that air embolism can complicate a variety of invasive procedures involving the vasculature, from central venous access placement to coronary artery bypass grafting [105,106]. In the context of CEPs, the presence of patent foramen ovale (PFO) plays an important contributory role [107]. Though rarely reported, air embolism due to decompression illnesses or due to iatrogenic causes may also cause coronary embolism.…”
Section: Miscellaneous Causesmentioning
confidence: 99%